Novel approaches to the prediction and diagnosis of pulmonary complications in the paediatric haematopoietic stem cell transplant patient. Issue 6 (18th December 2022) - Walker, Hannah; Shanthikumar, Shivanthan; Cole, Theresa; Neeland, Melanie; Hanna, Diane; Haeusler, Gabrielle M.
Abstract : Purpose of review: Haematopoietic stem cell transplant (HSCT) remains the only curative treatment option for many children with relapsed leukaemia, primary immunodeficiencies and haemoglobinopathies. Unfortunately, infectious and noninfectious pulmonary complications following HSCT continue to cause significant morbidity and mortality. This review will focus on recent advances in the field that enhance clinically available diagnostic tools and the role of novel diagnostic techniques. Recent findings: Research continues to highlight the role of standard diagnostic modalities, including imaging using computed topography chest and Fluorodeoxyglucose-positron emission tomography (FDG-PET) in the diagnosis of posttransplant pulmonary infections. Similarly, bronchoalveolar lavage using bronchoscopy to obtain samples for microbiological analysis remains an important tool in the clinical and diagnostic algorithm for these children. The application of more novel diagnostic techniques such as metagenomic next-generation sequencing and the use of specific biomarkers remain potential future tools in children in whom the aetiology of posttransplant lung disease is unknown. The impact of the pulmonary microbiome on infectious and noninfectious pulmonary disease post HSCT is a future research direction. Summary: Pulmonary infectious complications post HSCT remain a devastating complication for children and their families. Despite improvements in standard and novel diagnostic modalities, the aetiology of pulmonary disease remains unknown for many patients. There is an urgent need for ongoing collaborative research to bridge this critical knowledge gap and lead to better patient outcomes.